The extension of the arbitration agreement to non-signatories in Peruvian arbitration law - Eto Bardales, Gerardo (2020)
The purpose of the present paper is to analyze the extension of the arbitration agreement to non-signatories, taking into account that in principle arbitration is characterized by the consensus of the parties who sign the arbitration agreement, to submit to this mechanism to resolve their disputes. However, the complexity of the contracts in their different stages (negotiation, celebration and execution) means that in reality there are more parties involved than those who sign it in writing, since they have expressed their consent in a different way.